Pregnancy initiation in the rhesus macaque: Towards functional manipulation of the maternal-fetal interface - Golos Thaddeus G (BMC, 2004)
Abstract Nonhuman primates provide an important opportunity to define the mechanisms that contribute to the success of early pregnancy. We have focused for several years now on defining the expression of novel placental major histocompatibility complex (MHC) class I molecules. In parallel, we have used reagents against human immune cell markers to characterize the leukocyte population in the decidua and have demonstrated dynamic changes in these cell populations during the first 5 weeks of gestation. The challenge is to identify the possible role(s) of placental MHC class I in modifying/directing the maternal endometrial or systemic immune system in the post-implantation period. Foremost among the challenges is the difficulty in modifying placental function. In the instance of trophoblast surface proteins, passive immunization studies are feasible, although limitations include the empirical nature of this approach, as well as the inability to modify intracellular function. We have shown that using lentiviral vectors to effect preimplantation gene transfer for transgene expression in the placenta is not only feasible, but of good efficiency. In addition to transgene overexpression, robust approaches for knocking down/knocking out placental gene expression are essential. Recent developments in RNA interference approaches may allow "transient knockout" experiments. While the rhesus monkey has been our model of choice, currently there are limitations in the number of available female rhesus monkeys of reproductive age for research in early pregnancy. It is critical that the technologies for advanced study move forward in other species. The baboon has been used significantly in reproductive tract biology and early pregnancy research and important models have been developed for manipulation of the maternal-fetal interface. Additional characterization of other species, such as the cynomolgus and African green (vervet) monkey is critical. Given the limitations on antigen recognition when using human reagents, we also propose that the development of panels of primate-specific anti-leukocyte antibodies is essential for moving forward nonhuman primate reproductive research.